Beyond Charity - Nur Atika Atan; Rose Ruziana Samad; Fuadah Johari; Zurina Kefeli@ Zulkefli (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 2 Page (118-134)